1965
DOI: 10.1161/01.res.16.2.114
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Inflow and Oxygen Usage Following Cardiac Sympathetic Nerve Stimulation in Unanesthetized Dogs

Abstract: The effects of cardiac sympathetic nerve stimulation on coronary inflow were studied in previously operated conscious dogs, using electromagnetic flowmeters. Stimulation caused an increase of coronary inflow which was due mainly to an augmentation of flow during diastole. In systole, inflow changes were smaller and variable according to the strength of stimulation. The data presented indicate that an arteriolar dilatation may play a role in augmenting coronary inflow. In several instances, the increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

1971
1971
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(22 citation statements)
references
References 23 publications
3
19
0
Order By: Relevance
“…The concept that the coronary vasculature has the capacity to respond to sympathetic a-adrenergic activation elicited by direct electrical stimulation of sympathetic nerves to the heart (Beme et al, 1965;Granata et al, 1965;Feigl, 1967;Ross and Mulder, 1969;McRaven et al, 1971;Nayler and Carson, 1973;Feigl, 1975) or by the exogenous administration of a-adrenergic agonists Mohrman and Feigl, 1978) is firmly established. Recent evidence also indicates that a-adrenergic activation can reduce the diameter of large coronary arteries (Gerova et al, 1979;Vatner et al, 1980a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept that the coronary vasculature has the capacity to respond to sympathetic a-adrenergic activation elicited by direct electrical stimulation of sympathetic nerves to the heart (Beme et al, 1965;Granata et al, 1965;Feigl, 1967;Ross and Mulder, 1969;McRaven et al, 1971;Nayler and Carson, 1973;Feigl, 1975) or by the exogenous administration of a-adrenergic agonists Mohrman and Feigl, 1978) is firmly established. Recent evidence also indicates that a-adrenergic activation can reduce the diameter of large coronary arteries (Gerova et al, 1979;Vatner et al, 1980a).…”
Section: Discussionmentioning
confidence: 99%
“…Reflex sympathetic a-adrenergic activation has also been shown to play a significant role in the coronary vascular response to free-ranging, maximal exercise (Murray and Vatner, 1979), as well as static exercise (Aung-Din et al, 1981). Initial, transient reductions in either mean or stroke left coronary blood flow followed by pronounced coronary vasodilation have been reported in intact, conscious dogs in response to electrical stimulation of the stellate ganglion (Granata et al, 1965), noise and excitement (Rayford et al, 1965), and behavioral stress (Bergamaschi et al, 1973;Billman and Randall, 1981). However, the mechanisms responsible for the transient decrease in coronary blood flow were not investigated in those earlier studies (Granata et al, 1965;Rayford et al, 1965), and concomitant changes in heart rate and arterial pressure make it difficult to ascertain the extent to which sympathetic a-adrenergic constriction was involved in the coronary vascular response.…”
Section: Discussionmentioning
confidence: 99%
“…(18)(19)(20)(21)(22)(23), but a clinically important role has not generally been ascribed to them. Hamlin et al (9) demonstrated that coronary vasoconstriction caused by intravenous digoxin could be abolished completely by previous alpha adrenergic receptor blockade with phenoxybenzamine or by ganglionic blockade with mecamylamine.…”
Section: Methodsmentioning
confidence: 99%
“…In the stable state, metabolic regulators such as adenosine and prostaglandins are thought to be more important than neurogenic and myogenic factors (1)(2)(3)(4), though neurogenic mechanisms have been shown to alter coronary flow in awake and anesthetized animals as well. Both sympathetic and parasympathetic activation in animals produce coronary vasoconstriction and vasodilation (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), with a recent study suggesting the presence of alpha adrenergic tone on the coronary vasculature in the resting state (15). In man, reflex coronary vasoconstriction in response to a cold stimulus, mediated through an alpha adrenergic mechanism, has also been demonstrated (22).…”
Section: Introductionmentioning
confidence: 99%